Preparing Pre-Service Special Education Teachers to Facilitate Parent Involvement, Knowledge, and Advocacy: Considerations for Curriculum. (November 2019) - Strassfeld, Natasha M.
More than 40 years after passage of the Individuals with Disabilities Education Act (IDEA), some special education teacher preparation programs offer limited coursework on parent involvement, advocacy, or home–school collaboration. For pre-service special education teachers and/or novice special education teachers working with students with disabilities and their parents in practice, prior parent involvement coursework often enhances knowledge and abilities to provide resources, advocacy support, and insight. Yet, for this to occur in practice, special education teacher preparation program faculty should continue to consider how curriculum that instructs and provides resources regarding home–school collaboration, advocacy, conflict resolution, and federal legislation and programmatic support can enhance parent involvement. Therefore, this article examines IDEA parent involvement provisions, IDEA-mandated and federally funded conflict resolution options, and Parent Training and Information Centers that provide parents resources and support. Also, this article offers suggestions for teacher preparation faculty developing or refining parent involvement curricula.